Environmental Accounting and Economic Valuation of Natural Resources: The Impact of Commodity Extraction on Human Development in Producing Regions - Hastarini Dwi Atmanti (Perspectives on Advanced New Generations of Global and Local Economic Horizons, 2026)
The paradoxical nexus between natural resource abundance and socio-economic progression remains a critical hurdle for extractive-dependent economies. This investigation scrutinizes the impact of commodity extraction on human development within producing regions through environmental accounting and economic valuation. Utilizing an explanatory longitudinal-cross-sectional design, the research evaluates secondary data from 64 regencies in Indonesia, synthesizing fiscal realization reports from the Ministry of Finance (Oil, Gas, and Mineral Revenue Sharing/DBH) with Human Development Index (HDI) metrics from Statistics Indonesia (BPS). The study employs panel data regression with fixed effects and double-log transformation to measure revenue-to-welfare elasticity. Results reveal a significant yet inelastic correlation (), indicating substantial revenue inflows fail to proportionately catalyze human welfare advancements. By calculating Net Present Value (NPV) of ecosystem service losses, findings identify an "ecological debt" of 10.5%, where unrecorded environmental degradation costs (12%) significantly exceed regional reclamation allocations (1.5%). The study underscores diminished fiscal incentives and allocative inefficiencies as primary impediments to wealth transmission into social progress. Policy implications necessitate restructuring fiscal transfer formulas to integrate environmental performance and HDI efficiency as weighting variables. This research concludes that institutionalizing Natural Capital Accounting (NCA) is essential to internalize natural asset depreciation and prevent post-extraction structural insolvency in resource-producing regions.